The Influence of Technology in Educational Assessment in Indonesia - Irfan, Rifai (Pinisi Journal of Social Science, 2025)
The integration of technology into educational assessment in Indonesia represents a pivotal shift in the pedagogical landscape, reflecting broader global trends towards digitalization in education. This study explores the profound implications of this transition, analyzing how technological tools and platforms are reshaping assessment practices across Indonesian schools and universities. Historically, educational assessments in Indonesia have predominantly been paper-based and exam-centric, often emphasizing rote memorization over critical thinking and problem-solving skills. However, the advent of digital technologies has ushered in new possibilities for more dynamic, interactive, and learner-centered assessment methods. By employing a qualitative research approach, this investigation delves into the experiences and perspectives of educators, students, and policymakers, uncovering the multifaceted impacts of technology on assessment validity, accessibility, and pedagogical alignment. The findings reveal that while technology can enhance the efficiency and scope of assessments, it also poses challenges related to equity, digital literacy, and the need for robust infrastructural support. Furthermore, the study highlights the potential of technology to facilitate more formative, continuous, and authentic assessments, aligning more closely with educational goals that prioritize holistic learner development. In sum, this research contributes to a nuanced understanding of the transformative role of technology in educational assessment in Indonesia, offering insights into its benefits, limitations, and future directions.